Advances in Targeting Co-inhibitory and Co-stimulatory Pathways in Transplantation Settings: The Yin to the Yang of Cancer Immunotherapy - Kean, Leslie S. (Immunol Rev, 2017)
In the past decade, the power of harnessing T cell co-signaling pathways has become increasingly understood to have significant clinical importance. In cancer immunotherapy, the field has concentrated on two related modalities: First, targeting cancer antigens through highly activated chimeric antigen T cells (CAR-Ts) and second, re-animating endogenous quiescent T cells through checkpoint blockade. In each of these strategies, the therapeutic goal is to re-ignite T cell immunity, in order to eradicate tumors. In transplantation, there is also great interest in targeting T cell co-signaling, but with the opposite goal: in this field, we seek the Yin to cancer immunotherapy’s Yang, and focus on manipulating T cell co-signaling to induce tolerance rather than activation. In this review, we discuss the major T cell signaling pathways that are being investigated for tolerance-induction, detailing pre-clinical studies and the path to the clinic for many of these molecules. These include blockade of co-stimulation pathways and agonism of coinhibitory pathways, in order to achieve the delicate state of balance that is transplant tolerance: a state which guarantees lifelong transplant acceptance without ongoing immunosuppression, and with preservation of protective immune responses. In the context of the clinical translation of immune tolerance strategies, we discuss the significant challenge that is embodied by the fact that targeted pathway modulators may have opposing effects on tolerance based on their impact on effector versus regulatory T cell biology. Achieving this delicate balance holds the key to the major challenge of transplantation: lifelong control of alloreactivity while maintaining an otherwise intact immune system.